Perspectives on the doctrine of providence in some of Calvin" s sermons on Job - Potgieter, Pieter C. (Hervormde teologiese studies, 1998)
It is quite remarkable that Calvin addresses himself to the providence of God not only in his 'theological' works (eg Institutes), but particularly also in his more 'popular' works, for instance his correspondence and sermons. This is where the doctrine of providence is significantly contextualized. It is obvious that he takes up his topic in a most responsible manner, by which the 'providentia Dei' should not only comfort those who believe in Christ, but should also call for a responsible life before the countenance of God. Furthermore, for Calvin providence is not so much an issue to be 'explained', but rather a 'confession' related to the very heart of faith.